Editorial Notes - Girotto, Alice (Il Tolomeo, 2023)
The angles from which the contributions in this section look at the issue and the theoretical approaches they propose are quite diverse. There is first of all a terminological concern: what, specifically, does ‘Afro-European’ mean? Which people, and therefore which writers, fall into this category?